The Construction of Fantastic Time in the Novel “My Wife Is a Jinn” by Fawzi Abdu - Arab, asma; benramdane, fairouz (El Omda in Linguistics and Discourse Analysis, 2023)
This study tries to detect the structure of fantastic time in the novel of My wife is from the Djinn for Fawzi Abdo – with a character strange and odd – to see how effective its fraud and the structured through the monitoring of the narrative time technologies adopted by Fawzi Abdo, the writer, the start of the time paraspox of the" ethnicization and testing "technicians to move the silence and salvation and the concerts of the acquisition and technologies of acceleration, which is in the construction and deletion of contributing to the event and forming the event, as well as the standard on the characteristics of the times of the border time exceeded for everything that is familiar with usual and the incentive of the core differences that distinct it from the other than the other